2019
DOI: 10.3847/1538-3881/aafdb8
|View full text |Cite
|
Sign up to set email alerts
|

A Correction for GALEX Spectroscopic UV Flux Distributions from Comparisons with CALSPEC and IUE

Abstract: The CALSPEC database of absolute spectral energy distributions (SEDs) from the Hubble Space Telescope (HST) is based on pure hydrogen model atmosphere calculations for three unreddened white dwarf (WD) stars and represents the current UV flux calibration standard with a precision approaching 1% for well observed stars. Following our previous work to correct IUE fluxes, this paper provides an average correction for the GALEX spectral database that places GALEX fluxes on the current CALSPEC scale. Our correction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…After instrument commissioning the detection efficiency values in Figure 3 were multiplied by 0.7 when a preliminary comparison of observations of the star HD 30836 (π 4 Ori), which were made by allowing it to drift across the entrance slits of the spectrometers during commissioning, with published irradiance values from International Ultraviolet Explorer (IUE; Boggess et al, 1978; Bohlin, 1996; Bohlin & Bianchi, 2018) suggested that the ground calibration had overestimated instrument responsivity. This factor has been revised to 0.78 and 0.85 for Channel A and Channel B, respectively, based on above‐the‐atmosphere occultation observations of multiple stars (see section 4.7).…”
Section: Prelaunch Performancementioning
confidence: 99%
“…After instrument commissioning the detection efficiency values in Figure 3 were multiplied by 0.7 when a preliminary comparison of observations of the star HD 30836 (π 4 Ori), which were made by allowing it to drift across the entrance slits of the spectrometers during commissioning, with published irradiance values from International Ultraviolet Explorer (IUE; Boggess et al, 1978; Bohlin, 1996; Bohlin & Bianchi, 2018) suggested that the ground calibration had overestimated instrument responsivity. This factor has been revised to 0.78 and 0.85 for Channel A and Channel B, respectively, based on above‐the‐atmosphere occultation observations of multiple stars (see section 4.7).…”
Section: Prelaunch Performancementioning
confidence: 99%
“…Milone et al (1981) obtained a series of spectra of AI Phe during primary minimum with the International Ultraviolet Explorer (IUE) satellite. We downloaded the data from the IUE NEWSIPS archive 2 and applied the wavelength-dependent corrections suggested by Bohlin & Bianchi (2019) to put the flux on the CALSPEC scale. We created three trapezoidal filters with which to integrate the IUE spectra, the properties of which are given in Table 2.…”
Section: Ultraviolet Photometry and Flux Ratiosmentioning
confidence: 99%